EDUKASI GOOD FARMING PRACTICE BAGI PETERNAK SAPI POTONG DI KECAMATAN PAUH KOTA PADANG - Ferry Lismanto Syaiful; Khasrad Khasrad; Mangku Mundana; Rusdimansyah Rusdimansyah; Sumedi Sumedi (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2024)
Beef cattle are one of the livestock animals that produce meat with high economic value. In general, development faces many challenges because cattle farming is still managed traditionally by the community. Good Farming Practices (GFP) are guidelines for farmers in conducting livestock farming businesses. The objectives of this activity are: to increase the community's knowledge about the application of good farming practices (GFP) to beef cattle to improve production performance and increase community income. This activity was conducted with the Mak Uniang Livestock Group in Rindang Alam, Koto Luar Village, Pauh District, Padang City. The method used is PRA (Participatory Rural Appraisal), where partner lecturers directly act as facilitators and can immediately facilitate the community/partners in the implementation of activities. The learning method used to achieve the target activities is the participatory method. The partners of this activity are the Mak Uniang livestock group and the community in Rindang Alam, Koto Luar Village, Pauh District, Padang City. The stages of the activity include socialization/extension, which consists of presenting material and discussions. The material provided includes good livestock management (good farming practices). This activity received a very positive response and enthusiasm from the farmers. This is reflected in the farmers' interest in asking questions and their desire for technical guidance to promote sustainable farming. Additionally, the results of this activity show an increase in knowledge, understanding, and skills of the partners in implementing good farming practices (GFP) for beef cattle. The farmers have even committed to implementing what was conveyed by the speakers regarding the application of good farming to their cattle.